REVITALIZING WORKFORCE DYNAMICS: HOW TRANSFORMATIONAL LEADERSHIP SHAPES COMMITMENT AND DRIVES PERFORMANCE - Oktapiani, Marliza; Farida; Rupa, Martina Kaisriani; Nurhamzah; Hasibuan, Masnilam (Branding: Jurnal Manajemen dan Bisnis, 2025)
An adaptive and innovative organizational culture is crucial to the sustainability and competitiveness of organizations in the face of external and internal environmental changes. In this context, leadership plays a central role as the primary driver of transforming values and work behaviors. Challenges arising in the process of revitalizing organizational culture require leaders to actively shape a clear direction for change and motivate all organizational elements to participate. This study aims to examine how leadership acts as an agent of change in rebuilding an organizational culture that is more responsive to the demands of the times. This study uses a qualitative approach that allows for an in-depth exploration of leadership dynamics and the cultural transformation process. Data were collected through a literature review from various relevant sources and explained thematically. The results show that leaders who are able to strengthen work values that support innovation and shape an adaptive collective mindset make a significant contribution to the revitalization of organizational culture. Clarity in organizational direction and open communication have been shown to increase the spirit of renewal among employees. Thus, transformative leadership is an important foundation in creating an organizational culture oriented towards sustainable change.